KAJIAN TENTANG PERKEMBANGAN E-BUSINESS TERHADAP PRAKTIK BISNIS - Herman Herman; Yakub Yakub (CommIT (Communication and Information Technology) Journal, 2010)
The simple reason that businesses use internet technology is for increasing and changing their main business processes. Most of companies have already grown from traditional business practices to e-business practices. The growth of internet affects the way of how the company changes their design, process, produce, market, and deliver the product. Product delivering process in digital way through internet is predicted to increase in various business sectors. In order to implement the e-business concept, a company needs at least one of their business partners matching six group type according to the rules and functions.Keywords: e-business, delivering process, digital